The Contributions of Social Stressors and Coping Resources to Psychological Distress Among Those Who Experienced Furlough or Job Loss Due to COVID-19. Issue 2 (May 2023) - Grace, Matthew K.
The COVID-19 pandemic precipitated a global economic recession resulting in widespread unemployment and worker furloughs. Using national survey data (n = 2, 000), this study examines whether and how employment-based discrepancies in financial strains, anticipatory stressors, and personal coping resources contribute to elevated psychological distress among those who experienced involuntary job displacement due to COVID-19. Disaggregating displaced workers into those who were furloughed and those who lost their job due to the pandemic, I find that both groups report more depressive symptoms and anger than the stably employed and respondents whose unemployment is not COVID-related. Greater financial strains and smaller reserves of coping resources contribute in varying degrees to heightened levels of distress found among displaced workers, however, anticipatory stress about economic security is the predominant factor driving disparities in psychological distress. These findings, and the central role of anticipatory stressors in shaping employment-based differences in mental health during the pandemic, are discussed.